Evaluation of total hip replacement - Rahman, F; Salam, MA; Ali, MI; Hossain, MA (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jan;16(1):77-80.The abstract of this article is available on the PubMed website